ECONOMIC ASPECTS OF THE ECOLOGICAL APPROACH TO THE DEVELOPMENT OF AGRICULTURE AT THE PRESENT STAGE - Dmitry K. Suchkov; Ilya V. Sorgutov; Nadezhda K. Gavrilieva; Alexander V. Grigoriev (Siberian Journal of Life Sciences and Agriculture, 2021)
The economic aspects of the development of the agro-industrial complex at the present stage play a significant role in shaping the well-being of any country, since the factor of seasonality and the need to allocate subsidies to support most agricultural enterprises often negatively affect the prospects for the development of the industry in question. At the same time, it should be noted that agro-industrial companies spend significant funds on recultivation and restoration of lands damaged by regular application of chemical fertilizers. Also, various biosystems are being destroyed, without which the implementation of various activities in the agro-industrial complex will be impossible: water resources are being depleted, representatives of fauna are dying, the structure of individual ecological networks is being disrupted. For this reason, the application of an ecological approach in the process of forming an economic strategy for the development of agriculture at the present stage becomes necessary, since if the status quo is maintained, the negative situation in agriculture may worsen in the next few years. For this reason, we consider it necessary to implement the main provisions of the Concept of Sustainable Development in the process of planning and implementing various areas of economic and production activities in the agricultural sector, since relying on the postulates declared by the Concept will expand the horizons of the industry’s development, improve the quality and volume of products produced and reduce its negative impact on the environment, thereby preserving the ecological balance in nature.